Essays on purchasing and supply management - Kern, Daniel; SpringerLink (Online service). (Wiesbaden Gabler Verlag Springer, 2011)
The recent past has seen a growing interest in supply chain management (SCM) topics. Despite the vast amount of published supply chain research, the need for the further refinement of SCM tools is even more relevant today. Numerous studies show that the theoretical SCM concepts still lack practical implementation in today?s business world. Through the empirical validation of SCM models and in-depth case studies, Daniel Kern provides an answer on how to implement the theoretical concepts into the day-to-day business of multinational corporations. The four essays cover research on inter-firm collaboration, supply risk management, purchasing competences and research on measuring and benchmarking SCM efforts.
Electronic reproduction.
Keywords: Business logistics -- Management; Economics; Economics/Management Science; Electronic books